2008
DOI: 10.1007/s10384-008-0573-3
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal injection of bevacizumab to treat neovascular glaucoma

Abstract: tendon, and it covered the tissue plane of the levator aponeurosis and the levator palpebrae superioris muscle.An excisional biopsy of the mass was performed to confi rm the diagnosis. During the surgery, a mass was found just beneath the orbital septum with an anterior intraorbital extension, and a biopsy specimen was removed. Histopathological comparison of the specimen was then made with the previous esophageal biopsy specimen from this patient. The eyelid biopsy revealed a moderately differentiated metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…5 Recent studies have reported that the off-label use of intravitreal (IV) injection of bevacizumab is an effective and safe treatment for NVG. [6][7][8][9][10][11][12][13][14][15] Intravitreal injection of bevacizumab leads to a dramatic regression of the new iris and angle vessels and a decrease in IOP, although these effects may be transient owing to the drug's short half-life. 16 The effects of bevacizumab on the vasculature of the anterior ocular segment, however, are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Recent studies have reported that the off-label use of intravitreal (IV) injection of bevacizumab is an effective and safe treatment for NVG. [6][7][8][9][10][11][12][13][14][15] Intravitreal injection of bevacizumab leads to a dramatic regression of the new iris and angle vessels and a decrease in IOP, although these effects may be transient owing to the drug's short half-life. 16 The effects of bevacizumab on the vasculature of the anterior ocular segment, however, are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…24 In the present study, the IOP showed a decrease in 3 of 4 eyes after IV bevacizumab injection. Previous studies 13 reported that IV bevacizumab injection leads to a reduction of the IOP in eyes with earlystage NVG. Three of 4 eyes in the present series exhibited IOPs within the reference range after IV bevacizumab injection, when dye leakage was minimal with FA.…”
Section: Commentmentioning
confidence: 90%
“…After the efficacy of intravenous bevacizumab on age-related macular degeneration was shown, it was administered intravitreally, 3,4 and the injection of intravitreous bevacizumab (IVB) began to be used widely for treatment of various ocular diseases, including branch retinal vein occlusion, 5,6 polypoidal choroidal vasculopathy, 7,8 retinal angiomatous proliferation, 9,10 myopic choroidal neovascularization (CNV), 11,12 CNV secondary to angioid streaks, 13,14 proliferative diabetic retinopathy, 15,16 and neovascular glaucoma. 17,18 Intravitreous bevacizumab can cause complications, including traumatic cataract, retinal detachment, and endophthalmitis, with the reported incidence of endophthalmitis ranging from 0.014% to 0.082%. 19 -24 Although several cases of sterile endophthalmitis have been reported, most of these cases have been sporadic, and in most instances, the inflammation subsided with no treatment or with topical treatment.…”
mentioning
confidence: 99%
“…Previous studies have identified several risk factors for NVG after vitrectomy, including obvious preoperative neovascularization of the iris/angle, male sex, and postoperative retinal detachment. 3 , 6 , 7 The reported treatments for NVG include intravitreal injection of an anti-vascular endothelial growth factor (anti-VEGF) agent, 8 10 additional retinal photocoagulation, and trabeculectomy or tube shunt surgery for closed-angle NVG or other conditions unresponsive to intraocular pressure (IOP) reduction therapy. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%